2023
DOI: 10.1371/journal.pone.0288694
|View full text |Cite
|
Sign up to set email alerts
|

Mapping, intensities and future prediction of land use/land cover dynamics using google earth engine and CA- artificial neural network model

Abstract: Mapping of land use/ land cover (LULC) dynamics has gained significant attention in the past decades. This is due to the role played by LULC change in assessing climate, various ecosystem functions, natural resource activities and livelihoods in general. In Gedaref landscape of Eastern Sudan, there is limited or no knowledge of LULC structure and size, degree of change, transition, intensity and future outlook. Therefore, the aims of the current study were to (1) evaluate LULC changes in the Gedaref state, Sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In this work, to predict changes in LULC by 2030 and 2050, the combined CA-ANN model was used, and studies were carried out using the MOLUSCE plugin of QGIS software, the effectiveness and reliability of which have been confirmed in many works [32][33][34][35][36][37]. In our case, the results of the validation of the forecast model also turned out to be relatively high (≥0.85), which gives grounds to consider the effects of modeling future changes in LULC quite reliable since 0.75 is regarded as an acceptable threshold [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, to predict changes in LULC by 2030 and 2050, the combined CA-ANN model was used, and studies were carried out using the MOLUSCE plugin of QGIS software, the effectiveness and reliability of which have been confirmed in many works [32][33][34][35][36][37]. In our case, the results of the validation of the forecast model also turned out to be relatively high (≥0.85), which gives grounds to consider the effects of modeling future changes in LULC quite reliable since 0.75 is regarded as an acceptable threshold [36].…”
Section: Discussionmentioning
confidence: 99%
“…Because CA-ANN is based on "what-if" scenarios, it is suitable for land change modeling studies [32]. It is believed that CA-ANN accurately represents the complex spatial inhomogeneities of LULC [33]; therefore, it is successfully used to evaluate future LULC transformations. At the same time, the Modules for Land-Use Change Simulation (MOLUSCE) plugin, as part of QGIS, is often used to model future LU generations based on CA-ANN [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The NDVI was assessed and used to increase classification accuracy. The NDVI threshold for the separation of vegetation and the historical high-resolution images on Google Earth platform were used as a reference data [ 41 , 52 ] The onscreen digitization approach has been widely used and reported in previous studies for obtaining LULC classes, and it has been found to be reliable and accurate [ 53 , 54 ]. We generated 202 samples for the year 2016 and 216 samples for the year 2022, representing the five LULC classes.…”
Section: Methodsmentioning
confidence: 99%
“…We selected Random Forest as the classification algorithm as it has been widely used on land use and land cover change investigations ( Alencar et al, 2020 ; Souza et al, 2020 ; Osman et al, 2023 ; Shimabukuro et al, 2023 ). Also, this algorithm is good at handling outliers and noisy datasets, has high processing speed ( Jin et al, 2018 ), has good performance with complex datasets ( Belgiu & Drăguţ, 2016 ), and has higher accuracy than other algorithms ( Sheykhmousa et al, 2020 ; Talukdar et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%